2021
DOI: 10.1093/cvr/cvab109
|View full text |Cite
|
Sign up to set email alerts
|

Anxa1 in smooth muscle cells protects against acute aortic dissection

Abstract: Aims Acute aortic dissection (AAD) is a life-threatening disease with high morbidity and mortality. Previous studies have showed that vascular smooth muscle cell (VSMC) phenotype switching modulates vascular function and AAD progression. However, whether an endogenous signaling system that protects AAD progression exists, remains unknown. Our aim is to investigate the role of Anxa1 in VSMC phenotype switching and the pathogenesis of AAD. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Anxa1 blocks the production of a synthesis phenotype of VSMCs by downregulating the JunB/MYL9 pathway, which leads to increased inflammation and enhanced matrix metalloproteinase (MMP) production, resulting in increased elastin degradation and subsequent worsening of acute aortic dissection (AAD) [ 75 ]. It was revealed that 5’-tiRNA-Cys-GCA was decreased in human and mouse aortic dissection models, and 5’-tiRNA-Cys-GCA overexpression inhibited the proliferation and migration of vascular smooth muscle cells through STAT4, upregulated contractile markers, reduced the incidence of angiotensin II and β-aminopropionitrile-induced aortic dissection (AD) in mice and prevented its deterioration [ 76 ].…”
Section: Cardiovascular Diseases Associated With Vsmcs Phenotypic Swi...mentioning
confidence: 99%
“…Anxa1 blocks the production of a synthesis phenotype of VSMCs by downregulating the JunB/MYL9 pathway, which leads to increased inflammation and enhanced matrix metalloproteinase (MMP) production, resulting in increased elastin degradation and subsequent worsening of acute aortic dissection (AAD) [ 75 ]. It was revealed that 5’-tiRNA-Cys-GCA was decreased in human and mouse aortic dissection models, and 5’-tiRNA-Cys-GCA overexpression inhibited the proliferation and migration of vascular smooth muscle cells through STAT4, upregulated contractile markers, reduced the incidence of angiotensin II and β-aminopropionitrile-induced aortic dissection (AD) in mice and prevented its deterioration [ 76 ].…”
Section: Cardiovascular Diseases Associated With Vsmcs Phenotypic Swi...mentioning
confidence: 99%
“…Thus, AnxA1 deficiency in SMCs aggravates acute aortic dissection (AAD) in mice (Zhou et al, 2022). In addition, Ac2-26 administration decreased AAD incidence in AnxA1 −/− mice decreasing SMCs phenotypic switching to a secretory phenotype (Zhou et al, 2022). Taken together, in vivo studies reveal that administration of AnxA1 or derived peptides could serve to prevent pathological vascular remodeling.…”
Section: Figurementioning
confidence: 99%
“…AnxA1 plays an important role in maintaining SMCs homeostasis and protection against acute aortic dissection. Thus, AnxA1 deficiency in SMCs aggravates acute aortic dissection (AAD) in mice (Zhou et al, 2022). In addition, Ac2-26 administration decreased AAD incidence in AnxA1 −/− mice decreasing SMCs phenotypic switching to a secretory phenotype (Zhou et al, 2022).…”
Section: Figurementioning
confidence: 99%
“… 56 Zhao et al recently showed that Annexin A1 mitigated myocardial ischemia-reperfusion injury by activating signal transducer and activator of transcription 3 (STAT3) signaling pathway to suppress polymorphonuclear neutrophil infiltration and myeloperoxidase activity. 57 Purvis et al elegantly suggested that recombinant human Annexin A1 may represent a novel candidate for type-2 diabetes and/or its complications via mediating the RhoA activity, which restores insulin receptor substrate 1 (IRS1) signal transduction. 58 As the predominant strategy that treat fibrosis in various organs, anti-inflammatory response gathers multitudinous attention.…”
Section: Annexin A1mentioning
confidence: 99%